2020
DOI: 10.1016/j.cmi.2020.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up blood cultures are associated with improved outcome of patients with gram-negative bloodstream infections: retrospective observational cohort study

Abstract: Objectives: We examined factors associated with follow-up blood cultures (FUBCs) in patients with monomicrobial Gram-negative (GN) bloodstream infection (BSI) and investigated the impact of FUBCs on therapeutic management and patient outcome. Methods: A retrospective cohort analysis was conducted of adult patients diagnosed with GN-BSI at a tertiary-care university hospital during 2013e2016. FUBCs performed between 24 hours and 7 days after index BCs was the exposure variable. Risk factors for 30-day mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 19 publications
5
69
1
Order By: Relevance
“…Recent studies revealed that when FUBCs were performed in cases of gram-negative bloodstream infection, they were associated with improved clinical outcomes [13,14]. However, the proportion of FUBCs performed was relatively low (17.6-68%) compared to our present study (86.2%).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Recent studies revealed that when FUBCs were performed in cases of gram-negative bloodstream infection, they were associated with improved clinical outcomes [13,14]. However, the proportion of FUBCs performed was relatively low (17.6-68%) compared to our present study (86.2%).…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, our findings alone will not be sufficient to change routine practice. As discussed above, recent studies have shown that FUBC was associated with improved outcome of GNB [13,14], but these results couldn't be applied to the uncomplicated GNB. Further investigations such as a prospective randomized control study should be conducted to reveal the exact clinical impact of FUBC in GNB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies suggested low yield of FUBC in most patients with GN-BSI [6À9], whereas two more recent investigations demonstrated potential benefit from FUBC [10,11]. In an observational cohort study of GN-BSI in Italy, Giannella and colleagues reported significantly lower mortality in patients with GN-BSI who had FUBC obtained than those who did not have FUBC [10]. Maskarinec and colleagues demonstrated similar results in a large multicenter cohort in North Carolina [11].…”
Section: Introductionmentioning
confidence: 89%
“…However, the role of FUBC in the management of gram-negative BSI (GN-BSI) remains controversial. Prior studies suggested low yield of FUBC in most patients with GN-BSI [6À9], whereas two more recent investigations demonstrated potential benefit from FUBC [10,11]. In an observational cohort study of GN-BSI in Italy, Giannella and colleagues reported significantly lower mortality in patients with GN-BSI who had FUBC obtained than those who did not have FUBC [10].…”
Section: Introductionmentioning
confidence: 99%